Social norms, third-party observation and third-party reward - Matthias Sutter; Peter Lindner; Daniela Platsch (University of Innsbruck, Department of Public Finance, 2009)
This paper examines the influence of third-party observation and third-party reward on behavior in an experimental prisoner's dilemma (PD) game. Whereas the existing literature on third-party intervention as a means to sustain social norms has dealt almost exclusively with third-party punishment, we show that both third-party observation and third-party reward have positive effects on cooperation rates, compared to a treatment where no third party is involved. Third-party reward is more effective in increasing cooperation than third-party observation. However, rewards are given too late to prevent a steady downward trend of cooperation rates.
Keywords: C72; C91; 330; Social norms; third-party reward; third-party observation; prisoner?s dilemma experiment; Soziale Norm; Gefangenendilemma; Nichtkooperatives Spiel; Theorie